Electrical Power Potential and Installation of Picohydro Turbine-Generator - Orrsani Rateeila (Akademi Sertifikasi Profesi Internasional, 2023)
The 2014 National Energy Policy and the 2017 National Energy General Plan represent the government's dedication to advancing new and renewable energy capabilities. The policy aims to optimize the utilization of clean and renewable energy sources, particularly hydropower. This community service initiative aims to harness hydropower by assessing its electrical potential and developing mechanical electrical components to convert water's energy into electricity. The activity will take place in the village, utilizing one of the various altitudes of the river flow. The measurements conducted yielded an elevation of 1 meter and a discharge of 0.1 m³/s, resulting in a potential electrical power of around 600 watts. The generating facility selects generators and manufactures turbines based on the assessment of power potential. The employed methods are (1) quantifying the river's flow, (2) assessing the height of the fall (head) at the powerhouse site, (3) determining the potential for electric power, (4) fabricating turbines, and (5) placing turbine-generators within the powerhouse. The outcomes of this endeavor include the establishment of a power plant, the fabrication of turbines, and the installation of turbine-generators utilizing hydropower potential. The installation of turbine generators in this power plant represents the initial phase, which will be followed by the subsequent phase involving the building of water channel dams, penstocks, and electricity distribution for street lighting.